IMPROVING READING COMPREHENSION AND SPEAKING PERFORMANCE OF THE EIGHTH GRADERS USING ICM - SAPUTRA, EKO (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2020)
The aim of this experimental study was to investigate whether or not there were significant improvements in students’ reading comprehension and speaking performance after being taught by using Instructional Conversation Method. This study also aimed to see the significant difference in reading and speaking achievements between the students who got the treatment and those who did not. Sixty eight eighth graders with the same reading level were selected as the sample and were divided equally into experimental and control groups. Pretest and posttest were given to both groups, but the treatment was only for the experimental group. The data obtained from reading comprehension and speaking pretest and posttests in both groups were analyzed by using paired and independent sample t-tests. The result showed that after the students were taught by using ICM there were significant improvements in their reading and speaking achievements. There were also significant differences in reading and speaking achievements between both groups. In conclusion, ICM could help students improve their reading comprehension and speaking performance.